TRANSFORMATIONS OF SENSOMNESTIC DISTURBANCES OF THE VISUAL ANALYZER IN CHILDREN WITH PERINATAL ENCEPHALOPATHY - Salmanova, S.Z. (World of Medicine and Biology, 2023)
The leading causes of blindness and visual impairment in children is cerebral visual impairment. Perinatal encephalopathy lesions are the main risk factors of this pathology. The purpose of the study was to determine cause-effect relationships of ophthalmic and neurological indices in infants with perinatal encephalopathy. This work is based on the results of a comprehensive dynamic examination of 300 children with perinatal encephalopathy. A complex ophthalmic examination included: assessment of behavioral visual responses, retinoscopy, determination of the angle of deviation, direct ophthalmoscopy, visual evoked potentials and electroretinography. The observation period was 3 years (the first examination-in children aged up to 3 months, and then repeated at 6–12 months. The results showed that in children with perinatal encephalopathy at the age under 3 months, deviations of sensomnestic rates are observed in 35 % of cases. Electrophysiological differential criteria of delayed visual maturation syndrome and visual deficiency syndrome have also been identified, characterized by delayed visual maturation syndrome – lack or instability of clear differentiation of component N2; registration LN2≥155ms; AN2≤AP2 – at 3 months (or later); visual deficiency syndrome – lack or instability of a clear differentiation of component N1; registration LP2≥135ms; AN2≤AP2 – at 6 months (or later). The deficiency of short-latent visual afference is one of the mechanisms of the increasing trend where the threshold for convulsive brain activity in children with perinatal encephalopathy is reduced.